(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Assaha DVM, Petang LY. 2024. Bone meal enhances the growth and yield of the tomato cultivar Cobra F1 by increasing fruit Ca content and alleviating blossom-end rot. Asian J Agric 8: 70-77. Bone Meal (BM) is a cheap organic fertilizer rich in Ca, which can be important for tomato production to counter the fruit’s Blossom-End Rot (BER) disorder. The present study evaluated the effect of cow bone meal on the growth and yield of the Cobra F1 tomato variety. Therefore, to accomplish this, field plots randomly treated with BM (0, 143, 286, 429, and 572 kgha-1) were sown with 30-day-old uniform-sized tomato seedlings. At the end of 8 weeks of treatment, plant height, number of leaves, fresh and dry vegetative biomass, and yield (fruit weight) were measured. The results obtained revealed that BM, at especially 572 kgha-1, significantly elevated plant height (48%), leaf number (45%), root fresh weight (2.1-fold), stem fresh weight (27%), leaf and stem dry weight (27 and 51%, respectively), fruit weight per plant (2.1-fold), and up to 14% increase in fruit Ca concentration. BER affected control plants but did not affect BM-treated plants. Together, these results indicate that BM can significantly increase vegetative growth and yield of tomato void of BER; hence, it should be very suitable to enhance tomato production.